NUSYUZ DALAM PERSPEKTIF AGAMA DAN NEGARA: SEBUAH UPAYA PENGHAPUSAN KEKERASAN DALAM RUMAH TANGGA - Akhmad Rudi Maswanto (Program Studi Hukum Keluarga Islam, Fakultas Syariah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2023)
Marriage in Islam is not solely a relationship between husband and wife, but more than that Islam views marriage as an act of worship value because every action that each spouse performs when fulfilling his rights and obligations in marriage is an act of good and bad value. Rights and obligations in the household that do not work as stipulated in Islam are known as nusyuz. The problem of nusyuz in Indonesia has always been associated with the wife, as well as in the legal arrangements, namely in the Compilation of Islamic Law (KHI) only regulates the nusyuz of the wife. Nusyuz that occurs in the household can come from the side of the wife or the side of the husband. According to Soerjono Soekanto, whether or not law enforcement is effective in society is determined by several factors, namely law enforcement, legal facilities, legal awareness, legal rules, and legal culture. The law on domestic violence enacted through the law has not been fully enforced effectively to provide protection for victims of domestic violence.